Consumer protection and contingent charges. - Armstrong, M; Vickers, J (American Economic Association, 2012)
Contingent charges for financial services, such as fees for unauthorized overdrafts, are often controversial. We study the economics of contingent charges in a stylized setting with naive and sophisticated consumers. We contrast situations where the naive benefit from the presence of sophisticated consumers with situations where competition works to subsidize the sophisticated at the expense of the naive, arguably unfairly. The case for regulatory intervention in these situations depends in good part, but not only, on the weight placed on distributional concerns. The economic and legal issues at stake are well illustrated by a case on bank charges recently decided by the U.K. Supreme Court.